Six ingredients with Six Sisters' Stuff : 100+ fast and easy family meals. (Shadow Mountain, 2019)
No matter what your skill level, the recipes in this book will help you master meals with incredible flavor combinations. All the recipes use only six ingredients-- or less! There are one-pot meals, slow-cooker creations, no-bake recipes, and even "kid-approved" recipes that are perfect for the picky eater in your house.